2017
DOI: 10.1161/jaha.116.005460
|View full text |Cite
|
Sign up to set email alerts
|

Short Length of Stay After Elective Transfemoral Transcatheter Aortic Valve Replacement is Not Associated With Increased Early or Late Readmission Risk

Abstract: BackgroundElderly patients undergoing transcatheter aortic valve replacement (TAVR) are at risk of hospital readmission postprocedure. It is not known whether the index hospital length of stay and, specifically, early discharge post‐TAVR is associated with an increased risk of readmission. We hypothesized a nonlinear relationship whereby both short and long lengths of stay were associated with increased readmission risk.Methods and ResultsWe performed a retrospective multicenter cohort analysis of patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“… also concluded that early discharge after colorectal surgery may be implemented without any adverse effect on readmission rates based on the analyses of NSQIP data. The majority of studies on other types of surgery, such as joint arthroplasty, bariatric surgery, lobectomy and aortic valve replacement has also shown no detrimental effects from early discharge . The present study adds to the evidence supporting the hypothesis that early hospital discharge and post‐discharge outcomes are compatible, even for a morbid oncological surgery such as RC.…”
Section: Discussionsupporting
confidence: 63%
“… also concluded that early discharge after colorectal surgery may be implemented without any adverse effect on readmission rates based on the analyses of NSQIP data. The majority of studies on other types of surgery, such as joint arthroplasty, bariatric surgery, lobectomy and aortic valve replacement has also shown no detrimental effects from early discharge . The present study adds to the evidence supporting the hypothesis that early hospital discharge and post‐discharge outcomes are compatible, even for a morbid oncological surgery such as RC.…”
Section: Discussionsupporting
confidence: 63%
“…71 Early (< 3 days) and next-day discharge have been shown to be feasible and safe, [72][73][74] with no increased risk of readmission within 30 days or 1 year. 75 As expected, most patients who experienced vascular or bleeding complications, or those who required insertion of a permanent pacemaker were not eligible for early discharge.…”
Section: Postprocedures Carementioning
confidence: 64%
“…Patients in that study underwent TAVR in Ontario between 2007 and 2014; the median length of stay was 6 days and 19% of hospital stays were <4 days. A patient‐level analysis revealed no relationship between length of stay and the 30‐day likelihood of readmission …”
mentioning
confidence: 96%
“…The timing of the studies by Dodson and by Sud, and our own study referencing the Nationwide Readmission Database, all point to a major limitation in our current ability to assimilate clinical data, given that all 3 may already be outdated. This problem is particularly vexing in a field that has been as dynamic as TAVR.…”
mentioning
confidence: 99%
See 1 more Smart Citation